Thermal Spray 1998: Proceedings From the International Thermal Spray Conference 1998
DOI: 10.31399/asm.cp.itsc1998p0187
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Properties of Tungsten Carbide Coatings Sprayed with Various HVOF Spray Systems

Abstract: The paper reports a series of experiments with various HVOF spray systems (Jet Kote, Top Gun, Diamond Jet (DJ) Standard, DJ 2600 and 2700, JP-5000) using different types of WC-Co and WC-Co-Cr powders. The microstructure and phase composition of powders and coatings were analyzed by optical and scanning electron microscopy and X-ray diffraction. Carbon and oxygen content of the coatings were determined in order to study the decarburization and oxidation of the material during the spray process. Coatings were al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…WC-Co-based coatings obtained by thermal spray are widely used in mechanical applications where a high resistance to sliding wear is required [11][12][13]. In particular, high velocity oxy-fuel (HVOF) thermal spraying is regarded as one of the best methods for depositing conventional WC-Co feedstock powders [14][15], in view of the good combination of higher deposition rate and lower temperature with respect to plasma deposition. These conditions determine a lower porosity and, therefore, a better wear resistance of the coatings [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…WC-Co-based coatings obtained by thermal spray are widely used in mechanical applications where a high resistance to sliding wear is required [11][12][13]. In particular, high velocity oxy-fuel (HVOF) thermal spraying is regarded as one of the best methods for depositing conventional WC-Co feedstock powders [14][15], in view of the good combination of higher deposition rate and lower temperature with respect to plasma deposition. These conditions determine a lower porosity and, therefore, a better wear resistance of the coatings [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, high velocity oxy-fuel (HVOF) thermal spraying is regarded as one of the best methods for depositing conventional WC-Co feedstock powders [14][15], in view of the good combination of higher deposition rate and lower temperature with respect to plasma deposition. These conditions determine a lower porosity and, therefore, a better wear resistance of the coatings [13][14][15]. The HVOF WC-Co-based coatings in the as-sprayed condition normally display a hardness in the range 1100-1200 HV, and a surface average roughness, R a , around 5 m, depending on the powder particles size and morphology and on the specific spraying parameters [16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…The decarburization reaction is not favorable but always occurs at facing of high temperature. More details concerning decar-burizeation of WC based coatings can be found in Ref [14][15][16][17][18]. In this study, the test results showed that the use of different binders could not achieve different results in decarburization.…”
Section: Resultsmentioning
confidence: 69%
“…Due to the low porosity, highly adherent coatings, and less oxide content, HVOF is the preferred thermal spray process for the chrome replacement. For the deposition of conventional Cr3C2 -NiCr feedstock powders, the HVOF thermal spray process considered the best method as the very high velocity of the flame shortens the time of interaction between flame and the powder [8]. It was concluded that CrC-NiCr HVOF coatings are superior in performance comparing to chrome plating.…”
Section: Case Study 4: Surface Properties Of Crn Coated Engine Cylindersmentioning
confidence: 99%